Highlights of the Impacts of Green and Sustainable Chemistry on Industry, Academia and Society in the USA. Issue 3 (1st July 2017) - Marteel-Parrish, Anne; Newcity, Karli M.
Trends such as population growth, climate change, urbanisation, resource scarcity, conservation of energy and water, and reduction of waste and toxicity have led to the development of sustainable practices in industry, education and society. The desire to improve ways of living, the need for performance materials, and the urgency to close the gap between developed and emerging nations have propelled creative and innovative solutions based on green and sustainable chemistry to the forefront. This article provides an overview of the main impacts of green chemistry on industry, academia and society in the USA in the past ten years, as well as a summary of the drivers and barriers associated with the adoption of green chemistry practices. It also describes how researchers, policy makers, educators, investors and industries can work together to "build innovative solutions that transform and strengthen the chemical enterprise" (1) while addressing environmental and social challenges. The goal of this article is to understand why green chemistry is still primarily viewed as Joel Tickner, Director of Green Chemistry and Commerce Council (GC3), University of Massachusetts, Lowell, USA, puts it: as "an environmental activity rather than one that, as experience shows, yields economic benefit, and it has yet to be integrated into the fabric of the chemical enterprise, educational systems, or government programs" (1).